The Role of Intellectual Capital and Entrepreneurial Characteristics as Innovation Drivers - Nadia Ugalde-Binda; Francisco Balbastre-Benavent; M. Teresa Canet-Giner; Naiara Escribá-Carda (Innovar: Revista de Ciencias Administrativas y Sociales, 2014)
Innovation and entrepreneurship are essential organizational strategies to find a way out of the world crisis affecting today’s firms. Thus, the study of how organizational factors, like intellectual capital or entrepreneur characteristics, affects the success of an innovative entrepreneurial project is of utmost importance in helping current organizations find a solution to this problem. Intellectual capital involves investment in human, structural and relational capital. Consequently, our research goal centres on analyzing the influence of intellectual capital as well as the personal characteristics of entrepreneurs on the innovation results. This phenomenon remains unexplored in the case of micro and small firms. Our paper focuses on a particular context where small firms represent a key role in the industry: the case of Costa Rica. We used both quantitative and qualitative methodologies in order to develop the analysis. Our first results show a positive and significant relationship between structural and relational capital and innovation results; also, we can observe a positive relationship between a general measure of intellectual capital and innovation results. The case study illustrates how human capital and, specifically, the characteristics of the entrepreneur have an important influence on firm results. Our work contributes to show the relevance of intellectual capital on innovation success, and results encourage practitioners to invest in structural and relational capital and also improve the degree of planning of activities to obtain better results in the long term.